2017
DOI: 10.1159/000485084
|View full text |Cite
|
Sign up to set email alerts
|

Cylindromatosis (CYLD), a Deubiquitinase, Attenuates Inflammatory Signaling Pathways by Activating Toll-Like Receptor 3 in Human Mesangial Cells

Abstract: Background/Aims: Cylindromatosis (CYLD), a deubiquitinase, negatively regulates nuclear factor-κB in various cells. However, its potential roles in glomerular inflammation remain unclear. Because the activation of the Toll-like receptor 3 (TLR3)/type I interferon (IFN) pathways plays a pivotal role in chronic kidney diseases (CKD), we examined the role of CYLD in the TLR3 signaling in cultured human mesangial cells (MCs). Methods: We stimulated CYLD-silenced MCs with polyinosinic-polycytidylic acid (poly IC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Experiments using siRNA confirmed that this response was mediated by signaling via TLR3. Concerning type I IFNs, we have shown in prior works using cultured human GECs and mesangial cells that IFN-β synthesized de novo following TLR3 activation is a key in regional inflammatory cascades [8, 13-15, 20]. Indeed, induction of RIG-I, MDA5, and IL-6 expression was lagged behind the increase in IFN-β levels observed here, and knockdown of IFN-β resulted in decreased expression of these molecules.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…Experiments using siRNA confirmed that this response was mediated by signaling via TLR3. Concerning type I IFNs, we have shown in prior works using cultured human GECs and mesangial cells that IFN-β synthesized de novo following TLR3 activation is a key in regional inflammatory cascades [8, 13-15, 20]. Indeed, induction of RIG-I, MDA5, and IL-6 expression was lagged behind the increase in IFN-β levels observed here, and knockdown of IFN-β resulted in decreased expression of these molecules.…”
Section: Discussionsupporting
confidence: 47%
“…Furthermore, we previously noted intense glomerular expressions of RIG-I and MDA5, cytosolic sensors of viral RNA, in biopsy specimens from patients with proliferative LN, but only MDA5 and not RIG-I expression in specimens from patients with IgA nephropathy [19, 20]. Thus, activation of innate immunity, including the TLR3/RIG-I/MDA5 signaling axis, in the inflammatory process in residual glomerular cells is likely to be involved in the pathogenesis of some forms of GN, especially LN [5-8, 15]. With respect to the recruitment of circulating neutrophils by GECs, we previously observed that activation of TLR3/IFN-β signaling induces endothelial expression of CXCL1 and E-selectin [8], although this finding remains preliminary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CYLD is another DUB that removes K63-Ub chain from RIG-I to decrease the IFN production [26,27], but TBK1 and IKKε were also identified as the target of the deubiquitination of CYLD in 293 EBNA cells [27], resulting in the same effect. CYLD also interacted with IPS-1 to negatively regulate it, but did not deubiquitinate it [27].…”
Section: Cyldmentioning
confidence: 99%
“…Schmid et al found that in brain and peripheral blood of C57BL/6, the mRNA level of IFN-γ gene decreased with the knockdown of CYLD, while the serum concentration of IFN-γ increased [28]. A study conducted using human kidney mesangial cells (MC) showed slightly different results: silencing CYLD in MC cells and stimulating them with poly IC increased the toll-like receptor 3 (TLR3)-induced activation of RIG-I and MDA5 [26]; however, the level of mRNA of RIG-I and MDA5 actually decreased [26]. The authors speculated this difference to be caused by the change in cell line used [26], but further study is necessary to determine the cause.…”
Section: Cyldmentioning
confidence: 99%